The effect of difference type of electronic discussion on the achievement for secondary school students in Jeddah - Al-Malki, Tariq Ali; Al-Shehri, Ali Mohammad (Journal of Curriculum and Teaching Methodology, 2023)
The current study aimed to identify the impact of the different method of electronic discussions (discovery/ directed) on the academic achievement of secondary school students in the computer course in Jeddah, the semi-experimental approach was used, with a design based on two experimental groups, where the first group was using discovery-electronic discussions, and the second was using directed electronic discussions, and their impact on academic achievement was measured among a sample of students of the Scientific Institute in Jeddah and their number was 24 students who were divided equally into the two groups, and appropriate statistical treatments were identified, where arithmetic averages, the Wilcoxon test, Mann-Whitney- U Test, Eta-squared, and Black’s equation for adjusted gain were used. The results found that there were statistically significant differences at the level (0.01) between the average scores of the first experimental group (discovery discussions) and the second experimental group (directed discussions) in the achievement test, the value of (Eta-squared) amounting to (0.92), which indicates the presence of an effect Significant in favor of the first experimental group (discovery discussions). This is due to the fact that the students had the freedom to discuss, search for information and discover what links it with their previous experiences, and the researchers recommend activating electronic discussions of all kinds within educational environments because of the interaction they create between learners and give the learner a space of freedom, making him explore the links and relationships between the information he receives and his previous experiences.